Peru : Request for a Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Peru's Request for a Stand-By Arrangement (SBA). The authorities' program for 2002-03 seeks to set the basis for sustained high growth of output and employment and a steady reduction in poverty. The authorities are requesting IMF support for their program through an SBA to emphasize their commitment to sound policies. The IMF staff is of the view that the authorities' program is consistent with the objective of creating the conditions for sustained high rates of economic growth that would support a steady reduction in poverty.